Seventeenth and eighteenth-century fashion in detail - Hart, Avril; North, Susan; Davis, Richard; Davis, Leonie (London : V&A, 2009)
Contents: ##Stitching, seams, quilting, and cording ##Gathers, pleats, and looped drapery ## Collars, cuffs, and pockets ## Buttons ## Trimmings ## Applied decoration ## Slashing, pinking, and stamping ## Knitting, lace, and openwork ## Stomachers ## Gloves and shoes.
First published as Historical fashion in detail from the 17th and 18th centuries: London, V&A, 1998. First published in North America as Fashion in detail from the 17th and 18th centuries: Rizzoli, 1998.
boek